CO2 Hydrogenation over Oxide‐Supported PtCo Catalysts: The Role of the Oxide Support in Determining the Product Selectivity. (9th May 2016) - Kattel, Shyam; Yu, Weiting; Yang, Xiaofang; Yan, Binhang; Huang, Yanqiang; Wan, Weiming; Liu, Ping; Chen, Jingguang G.
Abstract: By simply changing the oxide support, the selectivity of a metal–oxide catalysts can be tuned. For the CO2 hydrogenation over PtCo bimetallic catalysts supported on different reducible oxides (CeO2, ZrO2, and TiO2 ), replacing a TiO2 support by CeO2 or ZrO2 selectively strengthens the binding of C, O‐bound and O‐bound species at the PtCo–oxide interface, leading to a different product selectivity. These results reveal mechanistic insights into how the catalytic performance of metal–oxide catalysts can be fine‐tuned.